All Days 2005
DOI: 10.2118/93536-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of a Successful Matrix Acid Stimulation Treatment in Horizontal Wells Using a New Diversion Surfactant in Saudi Arabia

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractMatrix acidizing of horizontal and multi-lateral wells is a challenging task for several reasons. First, oil reservoirs are heterogonous in nature and the presence of high permeability streaks is common. Proper diversion technique is always required to better distribute the injected acid across the target zone. Secondly, stimulation of horizontal wells requires injection of large volumes of acids. This will require using an effective corrosion inhibitor packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It has been found that the rheological properties are affected by numerous factors such as surfactant concentration, temperature, acid concentration, acid reaction products, solvents, salt concentrations, and other additives such as corrosion inhibitors. 16,17 Surfactants gels can be prepared using anionic, cationic, or amphoteric surfactants. 13 Amphoteric surfactants have been the subject of several lab 16 and fields studies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the rheological properties are affected by numerous factors such as surfactant concentration, temperature, acid concentration, acid reaction products, solvents, salt concentrations, and other additives such as corrosion inhibitors. 16,17 Surfactants gels can be prepared using anionic, cationic, or amphoteric surfactants. 13 Amphoteric surfactants have been the subject of several lab 16 and fields studies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Most of the production comes from heterogeneous carbonate reservoirs and long open hole productive sections are generally characterized by wide contrasting permeability. The majority of the damage occurs during the drilling process and the primary challenge for matrix acidizing is effective placement to maximize production potential.…”
Section: Introductionmentioning
confidence: 99%
“…The surfactant has a low viscosity in concentrated acid and shows increased viscosity as the acid spends. 5 The shear thinning nature of this material acts as a friction reducer to decrease surface treating pressure while pumping through small ID tubulars and allows it to regain maximum viscosity for diversion once in the wellbore. 8 Extensive laboratory testing has been done to better understand how viscoelastic surfactants work in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another paper reported on the successful use of this same viscoelastic surfactant to form a stable foam to successfully restore the injectivity of a seawater injector well in a carbonate reservoir in Saudi Arabia. 2 These recent successes show that certain viscoelastic surfactants have unique properties that make them particularly attractive for use as in-situ acid gelling agents for diversion. These include a more dependable diversion and better cleanup of the formation.…”
Section: Introductionmentioning
confidence: 99%